Tailoring the Redox Reactions for High‐Capacity Cycling of Cation‐Disordered Rocksalt Cathodes. (27th January 2021) - Yue, Yuan; Li, Ning; Ha, Yang; Crafton, Matthew J.; McCloskey, Bryan D.; Yang, Wanli; Tong, Wei
Abstract: Cation‐disordered rocksalts (DRXs) have emerged as a new class of high‐capacity Li‐ion cathode materials. One unique advantage of the DRX chemistry is the structural flexibility that substantially lessens the elemental constraints in the crystal lattice, such as Li content, choice of transition metal redox center paired with appropriate d 0 metal, and incorporation of F anion, which allows optimization of the key redox reactions. Herein, a series of the DRX oxyfluorides based on the Mn redox have been designed and synthesized. By tailoring the stoichiometry of the DRX compositions, high‐capacity cycling by promoting the cationic Mn 2+ /Mn 4+ redox reactions while suppressing those from anionic O is successfully demonstrated. A highly fluorinated DRX compound, Li1.2 Mn0.625 Nb0.175 O1.325 F0.675 (M0.625 F0.675 ), delivers a capacity of ≈170 mAh g −1 at C/3 for 100 cycles. This work showcases the concept of balancing the cationic and anionic redox reactions in the DRX cathodes for improved electrochemical performance through the rational composition design. Abstract : The emerging cation‐disordered rocksalt (DRX) cathode exhibits a superior advantage in terms of structural flexibility. A series of DRX compositions at varied fluorination are designed to promote the cationic Mn 2+ /Mn 4+ redox reactions. The highly fluorinated DRXs exhibit stable cycling at C/3 for 100 cycles, demonstrating the concept of tailoring the redox reactions for improved DRX cathode.